If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y+15=8y+11
We move all terms to the left:
6y+15-(8y+11)=0
We get rid of parentheses
6y-8y-11+15=0
We add all the numbers together, and all the variables
-2y+4=0
We move all terms containing y to the left, all other terms to the right
-2y=-4
y=-4/-2
y=+2
| 2x-79=-53 | | 8x-7+2x=63 | | 3+3a=5a-3 | | 7-7n=15+n | | -9x-6.8=-17.1 | | 5x+8.3=28.3 | | (3x^2)+4x=22 | | 3+2x=6(-x+9)-67 | | 114+4+5x=180 | | |–5x+7|=27 | | 100x=72.72 | | 5x+7-3x=32 | | 3.204=x | | 2x-5+6x=4x+3 | | 20/100=x/250 | | 60x=12^x | | 5x/2-15=-80 | | y+3/4=10 | | 3-10x=3x-5x^2 | | 8h^2-7h-9=0 | | 1.25x2=5.05 | | 3y+2(4y+11)=4(y-11)+7y | | 5w-(3w-8)=2(w+4) | | -8+4m=-36 | | 5v-11=3(v+10) | | 11/14=x/11 | | u/4-11=13 | | 17-2t=33 | | 5.50x+19=6.75x+11 | | 3r+18=18 | | 8q-11=6q+17 | | 2/11=4/x |